Early Middle Ordovician evidence for land plants in Argentina (eastern Gondwana) - Rubinstein, Claudia Viviana (2010)
The advent of embryophytes (land plants) is among the most important evolutionary breakthroughs in Earth history. It irreversibly changed climates and biogeochemical processes on a global scale; it allowed all eukaryotic terrestrial life to evolve and to invade nearly all continental environments. Before this work, the earliest unequivocal embryophyte traces were late Darriwilian (late Middle Ordovician; c. 463-461 million yr ago (Ma)) cryptospores from Saudi Arabia and from the Czech Republic (western Gondwana). Here, we processed Dapingian (early Middle Ordovician, c. 473-471 Ma) palynological samples from Argentina (eastern Gondwana). •We discovered a diverse cryptospore assemblage, including naked and envelope-enclosed monads and tetrads, representing five genera. •Our discovery reinforces the earlier suggestion that embryophytes first evolved in Gondwana. It indicates that the terrestrialization of plants might have begun in the eastern part of Gondwana. The diversity of the Dapingian assemblage implies an earlier, Early Ordovician or even Cambrian, origin of embryophytes. Dapingian to Aeronian (Early Silurian) cryptospore assemblages are similar, suggesting that the rate of embryophyte evolution was extremely slow during the first c. 35-45 million yr of their diversification. The Argentinean cryptospores predate other cryptospore occurrences by c. 8-12 million yr, and are currently the earliest evidence of plants on land.